Proximate Composition and Antimicrobial Activity of Kefir Produced from Cow’s and Almond Milk: Proximate composition and antimicrobial activity of kefir mixtures - Dr. Siti Raihanah Shafie; Jing Xuan Hew; Nurshahira Sulaiman (Journal of Tropical Life Science, 2023)
Fermented foods are an important diet component of people around the world. Kefir, or fermented milk, is popular worldwide due to its high nutritional value, with cow's milk being the common substrate for traditional kefir fermentation. However, the scarcity of animal-based milk in some countries, plus cultural, religious, and health reasons, have seen non-dairy milk kefir from almond milk gaining popularity among consumers globally. This study aimed to evaluate and compare the proximate composition and anti-microbial activity of kefir produced from 100% cow or 100% almond or an equal (1:1) mixture of both kinds of milk. This study used the AOAC 2000 method for the proximate analysis, while the agar well diffusion method examined the anti-microbial activity of the milk samples against Escherichia coli, Staphylococcus aureus, and Salmonella typhi. Results revealed that the three kefir samples showed significantly different (p<0.05) moisture, total dietary fiber, and fat contents and were within the CODEX acceptable range for kefir. All samples exhibited varying degrees of inhibition between the different pathogens. The diameters of the inhibition zone of the tested kefir samples were significantly different toward Salmonella typhi (p<0.05), with the mixture of almond and cow milk notably producing better inhibition towards all tested bacteria. The above-said milk mixture also gave a better overall nutrient profile (lower fat and higher fibre). While almond milk might be a suitable substrate for kefir, it was not effectively inhibitory for all bacteria. The overall results thus conveyed the promising use of almond and cow milk mixture as an alternative substrate for kefir fermentation, further supporting its potential use as a probiotics source.